Aportes de la concepción pedagógica de Francisco Ruiz Sánchez para una teoría motivacional perfectiva. (2019)
The present work aimed to indicate some aspects for understanding motivation from the dynamic fullness, that is, from the very purpose of the educational event. This re-search analyzes human motivation during the learning process in the light of the anthro-pological thought of Francisco Ruiz Sánchez. Through a hermeneutical methodology of his published and unpublished writings, we detailed the three main elements of the educational, motivational process: a) the method used, b) the proposal of good objects, and c) the awareness of the value of the object. It is concluded that motivation consti-tutes a relational aspect within the framework of a process in which cognition or inte-llectual tendency towards an object of good knowledge intervenes. This object has also been presented sensitively and can be perceived as valuable by the learner.